Improvement of Approaches to Labor Regulation in Service Sector Enterprises - REZNIKOVA, Olga Sergeevna; KOROLENKO, Julia Nikolaevna; ENENKO, Gennady Yurevich; TKACHENKO, Daria Vasilevna; REPNIKOVA, Valentina Mikhailovna (Journal of Environmental Management and Tourism; Vol 10 No 4 (2019): JEMT Volume X Issue 4(36) Summer 2019, 2019)
The article is devoted to the improvement of approaches to labor regulation in service sector enterprises. It has been established that labor regulation as one of the main directions of the personnel management system in modern economic conditions has not only remained relevant but continues to develop. It has been determined that for the improvement of labor regulation, it is necessary to ensure the following: centralized advanced training of regulation professionals, application of specialized regulation software, interconnection of the tariff system of labor payment and the system of its regulation. It has been proved that special attention should be paid to the formation of a scientifically substantiated methodological basis for labor not only at the level of service sector enterprises but also at the national level. It has been found that the special significance of regulation is related to the optimization of a service sector enterprise’s costs, implemented by setting time norms, quantity, service and manageability for all main operations ensuring the uninterruptible performance of the enterprise.